Assessment of the Progress in Small Ruminants' Community-Based Breeding Program Scaling and Exchange of Experiences Among Clusters - Belay, Berhanu; Getachew, Tesfaye; Haile, Aynalem (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
The Community-Based Breeding Program (CBBP), launched in 2009, offers an alternative approach to genetic improvement by focusing on selective breeding in smallholder settings. It achieves this by consolidating smallholder flocks to explore the genetic variability and facilitate targeted selection for better performance. Remarkable achievements have been made regarding increased productivity, income, genetic conservation, and family food and nutrition security. The engagement of universities has led to revamping the curriculum with CBBP and supported the establishment of climate-smart CBBP villages that enhanced teaching, research, and community services. The significant successes of the CBBP across various dimensions have prompted its expansion and the transformation of its operations from village/pilot stage to population/breed level. This could be achieved through clustering and scaling framework as a tool. Given the past achievements and the need for devising a clustering approach, a workshop was organized to understand the status breed level clusters and share experiences among clusters for future improvement. As part of the progress assessment, a workshop was held on July 31, 2024, and five clusters reported the progress and highlighted the need for enhanced support to achieve tangible results at the population level. The five clusters and a subsequent scaling initiative have brought key stakeholders together on a common platform and ensured the steering committee's formation to oversee the scaling efforts. The specific roles of the steering committee, as reported by cluster coordinators, included capacity building, genetic improvement standardization, genetic exchange, RAM distribution, and progress evaluation. The scaling framework has revealed the link and synergy of the components of the scaling framework, including CBBP, PU, finisher, and Market, that need to be strengthened. So far, five scaling clusters, Washera-Wollo (WaWo) Bongacho, Debub-Makelawi (DMI), Menz-Shewa, Borena-Omo-Konso (BOOM), have been established, and tangible activities are underway. Since 2021, 89,600 individuals have been beneficiaries of the scaling initiatives through breed-level clustering and improvement in five clusters. It was noted that there is a diversity of experiences in practicing clustering, scaling the small ruminant improvement practices, and reaching out to small ruminant keepers that have been shared for improvement.